Cristianesimo, nichilismo, kenosis - Vattimo, Gianni (Bollettino Filosofico, 2015)
The article aims to show Christianity as a nihilistic vocation of being itself, which is the meaning of the incarnation as kenosis (St. Paul to the Philippians). By comparing the reading of Christianity, and a conception of nihilism as the history of the West (where this is the land of the sunset being), the article proposes the reading of the kenotic core of incarnation as opening to proximity. In this way, Christianity/nihilism would not represent a weakening of the gospel message, even its most direct fulfillment.